Essential oil of Lippia alba (Mill.) N.E.Br. influences the germination, vigor and emergence of lettuce seeds - Thiesen, Leonardo Antonio; Schmidt, Denise; Pinheiro, Marcos Vinícius Marques; Holz, Ezequiel; Altissimo, Bruna Stringari; Holz, Evandro (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
Secondary metabolites are produced by certain plant species and may influence the development of some species through the action of allelopathic effects. Thus, the objective of this study was to evaluate the allelopathic effect of Lippia alba essential oil on the germination, emergence and vigor of seedlings of different batches of lettuce seeds. This experiment was conducted in a completely randomized design with a 3´5 factorial scheme consisting of three batches of seeds of the cultivar Grand Rapids® and five doses of L. alba essential oil (0, 0.25, 0.50, 0.75 and 1.00%) diluted in distilled water and homogenized in Tween® 80. Seed germination and vigor, in the laboratory (experiment I), and emergence, in a protected environment (experiment II), were evaluated. The results demonstrated that there was an inhibitory effect with a significant reduction of germination, vigor and seed emergence when L. alba essential oil was added starting at concentrations of 0.25%. The essential oil showed allelopathic potential over different lettuce seed lots, affecting germination, vigor and seed emergence.